Website-Based Online Sales Information System (E-Commerce) Case Study Apotek Mihardja Farma - Feri Alpiyasin; Mutiya Permatasari (Journal of Multimedia Technology and Applied Software, 2024)
In the management of sales transaction data, drug inventory, and purchase history using manual systems that are prone to errors and inefficiencies. Additionally, the limited payment methods and lack of comprehensive information about the drugs pose specific challenges. The data collection techniques used in this study include interviews, observations, and literature studies. The system development method employed is Object-Oriented Analysis and Design (OOAD) to model the system's analysis requirements. Thus, a web-based information system is needed to assist in the management of transactions, inventory, and automatic tracking of purchase history, as well as providing complete drug information. This web-based information system is expected to enhance operational efficiency and data accuracy, and provide better services to customers.